Use of Prehospital Early Warning Scores to Predict Short-Term Mortality: A Systematic Review - Naylor, David; Dicker, Bridget; Howie, Graham; Todd, Verity (Wiley, 2025)
Early Warning Scores (EWS) have been developed to identify patients at risk of deterioration. Although the application of EWS has become increasingly established in the prehospital setting, their use remains contentious. The aim of this systematic review is to summarise the most recent evidence on the predictive accuracy of the EWS for short-term mortality in adults in the prehospital setting. A systematic search was conducted using the Medline, CINAHL, and Scopus databases. Studies that evaluated the diagnostic accuracy of the prehospital Modified Early Warning Score, National Early Warning Score or National Early Warning Score 2 in predicting mortality were included. Secondary outcomes were intensive care unit (ICU) admission and hospital admission. The review included 16 studies published between 2012 and 2023, with the number of patients totalling 311 932. The literature indicated that prehospital EWS demonstrated a moderate to good diagnostic performance in predicting short-term mortality with an area under receiver operating characteristic curve ranging from 0.68 (95% confidence interval [CI]: 0.64-0.73) to 0.90 (95% CI: 0.82-0.97). Overall, diagnostic performance was higher for predicting mortality in short time frames (up to 48 h). The need to use relatively high cut-off points to identify at-risk patients may limit its use for the unselected patient populations found in the prehospital setting. The potential for under-triage and over-triage limits their use further. EWS should not replace structured clinical evaluation and judgement but may be useful as complementary and objective tools to aid the identification of patients at risk.
Keywords: early warning score; emergency service; mortality; out of hospital; paramedic; prehospital; 32 Biomedical and Clinical Sciences; 3202 Clinical Sciences; Patient Safety; 4.2 Evaluation of markers and technologies; Generic health relevance; 3 Good Health and Well Being; 1103 Clinical Sciences; 1117 Public Health and Health Services; Emergency & Critical Care Medicine; 3202 Clinical sciences; Humans; Early Warning Score; Emergency Medical Services; Mortality; Predictive Value of Tests; Humans; Mortality; Predictive Value of Tests; Emergency Medical Services; Early Warning Score; Humans; Early Warning Score; Emergency Medical Services; Mortality; Predictive Value of Tests